Phenomenology Study of Self Concept And Adaptation of Covid-19 Re-Infection Patient at Work Area of Binong Public Health Care Curug Sub District Tangerang: - Artharini, Moody; Suprapti, Fitriana; Kusumaningsih, Chatarina Indriati (Journal of Nursing Science Update (JNSU), 2023)
The COVID-19 pandemic and recurrent infections are ongoing worldwide, including Indonesia. Physical issues often occur with fever, nausea, cough, flu, diarrhoea, and body aches. The psychological issues that occur are anxiety, fear of death, worry about losing a job, and stigma from society. Repeated infection with COVID-19 can cause disturbances in self-concept, including self-identity, self-image, role performance, self-esteem, and adaptation. The study aimed to explore the self-concept and adaptation of patients with recurrent infection with COVID-19 in the work area of the Binong Health Center, Curug District, Tangerang Regency. The research design is descriptive phenomenology, with an in-depth interview technique of 15 participants using the Colaizzi method. The research results in the aspect of self-concept explored four (4) themes, namely 1). Age and gender affect the concern, which uses traditional herbal alternatives. 2) changes in body image do not cause concern, 3). awareness to limit roles in order to prevent transmission, 4). good self-health can increase self-esteem. The adaptation aspect found that the ability to adapt physically and psychologically speeds up the healing process of the disease. The study concludes that self-concept is not disturbed but feels worried when exposed to COVID-19 again. In the aspect of adaptation, it finds the need to balance physical, psychological, and spiritual conditions. Recommendations for further research to conduct qualitative research with Focus Group Discussion (FGD) regarding self-concept and adaptation of patients re-infected with COVID-19 for the third time.